Special Course «The Base of Socially-Pedagogical Work with Asocial Families» Studing in the Process of Primary School Future Teacher’s Training - Vornyk, Mariya (Pedagogical Discourse, 2013)
The content and methodical aspects of improving student’s knowledge and skills, while special course «The Base of socially-pedagogical work with asocial families» studing in the process of primary school future teacher’s training are reflected. The need for developing special course arose from the necessity to improve students ’knowledge of the foundations of social and educational work with antisocial families, as well as professional use in the practice of primary school teachers, enhance students’ knowledge of the problems of modern families, the socialization of primary school children from asocial families in the new social and cultural conditions , mastering the forms and methods of correction intrafamily relationships, improving educational opportunities for families of this type, to improve their functioning in modern society.